玉米醇溶蛋白/乳清蛋白纤维核复合纳米粒稳定Pickering乳液的制备与性质Preparation and property of zein/whey protein fiber core complex nanoparticle stabilized Pickering emulsions - 付思晗，齐玉堂，张维农，贺军波，张燕鹏，吕晓雅 FU Sihan, QI Yutang, ZHANG Weinong, HE Junbo, ZHANG Yanpeng, LYU Xiaoya (Zhongguo youzhi, 2022)
以玉米醇溶蛋白和乳清蛋白为原料，利用反溶剂共沉淀法制备玉米醇溶蛋白/乳清蛋白纤维核复合纳米粒，并与玉米油高速剪切制备Pickering乳液。探究了复合纳米粒在不同pH下的乳化性，以及复合纳米粒添加量对Pickering乳液粒径、微观形貌、储藏稳定性及流变学特性的影响。结果表明：玉米醇溶蛋白与乳清蛋白纤维核复合后乳化性显著提高，制备的Pickering乳液类型为水包油型；随着复合纳米粒添加量的增加，Pickering乳液粒径先减小后稍增大，添加量大于3 g（100 mL玉米油）后无显著性差异；在复合纳米粒添加量为4 g（100 mL玉米油）时，Pickering乳液油滴大小均一，储藏稳定性最好；Pickering乳液为假塑性流体，随复合纳米粒添加量的增加，表观黏度先减小后增大。 Using zein and whey protein as raw materials, the zein/whey protein fiber core complex nanoparticle were prepared by anti-solvent co-precipitation method and used for the preparation of corn oil loaded Pickering emulsions by high-speed shearing method. The emulsification property of complex nanoparticle was evaluated at different pH, and the effects of different nanoparticle dosages on the particle size, microscopic morphology, storage stability and rheological properties of Pickering emulsions were studied. The results showed that the emulsification property of zein/whey protein fiber core complex nanoparticle was significantly improved, and the prepared Pickering emulsions were oil-in-water emulsions. The particle size of Pickering emulsions reduced as the increase of complex nanoparticle dosage, and there was no significant difference above 3 g(100 mL corn oil). When the dosage was 4 g(100 mL corn oil), the Pickering emulsions had uniform oil droplets and the best storage stability. The Pickering emulsions were pseudoplastic fluid, and the apparent viscosity first decreased and then increased as the increase of complex nanoparticle dosage.